THE EFFECT OF JOB ASSESSMENT, WORK EXPERIENCE AND TRAINING ON EMPLOYEE MOTIVATION AT THE PUBLIC WORKS DEPARTMENT AND SPATIAL STRUCTURE OF KARIMUN REGENCY IN POST COVID-19 PANDEMIC WITH EMPLOYEE CAREER DEVELOPMENT AS INTERVABLE VARIABLES - Andykhatria, Andykhatria; Fachrudin, Fachrudin; Satriawan, Bambang; Khaddafi, Muammar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to determine the effect of performance appraisal, work experience and job training on employee work motivation with career development as an intervening variable. The population of this study were employees of the Public Works and Spatial Planning Office of Karimun Regency with a total sample of 80 respondents. Statistical data analysis using Structural Equation Modeling (SEM) with Smart PLS software version 3.0. The research data were collected using a questionnaire/questionnaire instrument. The results in this study found that performance appraisal directly has a positive and significant effect on employee career development with a p-value of 0.021 <0.05, work experience directly has a positive and significant impact on employee career development with a p-value of 0.029 < 0, 05, career development mediates the effect of work experience on employee motivation with a p-value of 0.040 < 0.05, and career development mediates the effect of job training on employee motivation with a p-value of 0.038 < 0.05. This study also shows that 56.2% of employees' work motivation variables are influenced by variables of performance appraisal, work experience and job training, while another 43.8% is influenced by other variables.